2011
DOI: 10.1097/aln.0b013e318232004b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single Recombinant Human Erythropoietin Injection on Transfusion Requirements in Preoperatively Anemic Patients Undergoing Valvular Heart Surgery

Abstract: A single intravenous administration of erythropoietin and an iron supplement 1 day before surgery significantly reduced the perioperative transfusion requirement in anemic patients undergoing valvular heart surgery, implicating its potential role as a blood conservation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
146
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 36 publications
3
146
1
1
Order By: Relevance
“…Although there have been many studies published, many controversies remain about the optimal protocol. Some authors proved that administration of rH-EPO alone or in addition to autologous blood donation could reduce the number of red blood cells transfused [9][10][11]. Conversely, some other authors found that postoperative use of lone rh-EPO did not have this effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many studies published, many controversies remain about the optimal protocol. Some authors proved that administration of rH-EPO alone or in addition to autologous blood donation could reduce the number of red blood cells transfused [9][10][11]. Conversely, some other authors found that postoperative use of lone rh-EPO did not have this effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated substantial benefits with the use of EPO, including decreased transfusion requirements and lower mortality in critically ill patients and in patients with gastrointestinal cancer [56,57]. Beneficial effects were demonstrated with as little as a single dose of EPO and iron one day prior to cardiac surgery in a recent study [58]. The enthusiasm for the use of EPO, however, has been curbed by inconsistent success with EPO [59], and by serious concerns about the adverse effects of EPO.…”
Section: Preoperative Optimization Of Patientsmentioning
confidence: 99%
“…1 In this issue of ANESTHESIOLOGY, Yoo et al report results of a singlecenter randomized controlled trial (RCT) of preoperatively anemic valvular heart surgery patients who a day before surgery received either 500 IU/kg of IV recombinant human erythropoietin ␣ (rhEPO) plus iron supplement (n ϭ 37), or a placebo bolus of normal saline (n ϭ 37). 2 Interestingly, despite the short interval between rhEPO administration and initiation of surgery (16 -24 h), subjects in the rhEPO group were significantly less likely than subjects in the placebo group to receive packed erythrocyte (PRBC) transfusions during the perioperative period spanning surgery and the first 4 postoperative days (59% compared with 86%; P ϭ 0.009). 2 Furthermore, subjects in the rhEPO group who received PRBCs were transfused with significantly fewer units than subjects in the placebo group (1.6 Ϯ 0.9 units/patient vs. 3.7 Ϯ 2.1 units/patient; P ϭ 0.004).…”
mentioning
confidence: 99%
“…2 Interestingly, despite the short interval between rhEPO administration and initiation of surgery (16 -24 h), subjects in the rhEPO group were significantly less likely than subjects in the placebo group to receive packed erythrocyte (PRBC) transfusions during the perioperative period spanning surgery and the first 4 postoperative days (59% compared with 86%; P ϭ 0.009). 2 Furthermore, subjects in the rhEPO group who received PRBCs were transfused with significantly fewer units than subjects in the placebo group (1.6 Ϯ 0.9 units/patient vs. 3.7 Ϯ 2.1 units/patient; P ϭ 0.004). 2 The results of this RCT are encouraging regarding potential for rhEPO to be used as an effective component of multimodal efforts to minimize perioperative blood transfusions in anemic patients undergoing valvular heart surgeries.…”
mentioning
confidence: 99%
See 1 more Smart Citation